Evidence for a multivalent effect in inhibition of sulfatases involved in lysosomal storage disorders (LSDs). Issue 69 (11th July 2016) - D'Adamio, G.; Matassini, C.; Parmeggiani, C.; Catarzi, S.; Morrone, A.; Goti, A.; Paoli, P.; Cardona, F.
Abstract : New targets sensitive to multivalency: synthesis of nonavalent pyrrolidine iminosugars. Abstract : Two newly synthesized nonavalent polyhydroxylated pyrrolidine iminosugars are the first examples of multivalent inhibitors of GALNS and IDS lysosomal enzymes, whose deficiency leads to Morquio A syndrome and Hunter disease, respectively, and pave the way to a pharmacological chaperone or stabilizing enzyme therapy for these LSDs.